2018
DOI: 10.1111/jdv.14842
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with delayed referral for infantile hemangioma necessitating propranolol

Abstract: This study adds to our understanding regarding delayed referral and has identified targets for future information campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Our data showed a notable incidence of vermilion IHs. The sex ratio of female to male cases of lip IHs was 1.4 : 1, and this result is in line with previously published data 7,8,9 . Although it is reported that low birth weight appears to be the most significant risk factor for IHs, with a 40% increase in risk for every 500‐g decrease in birth weight, 10,11 none of the patients in the current study weighed less than 2.0 kg.…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed a notable incidence of vermilion IHs. The sex ratio of female to male cases of lip IHs was 1.4 : 1, and this result is in line with previously published data 7,8,9 . Although it is reported that low birth weight appears to be the most significant risk factor for IHs, with a 40% increase in risk for every 500‐g decrease in birth weight, 10,11 none of the patients in the current study weighed less than 2.0 kg.…”
Section: Discussionsupporting
confidence: 92%
“…Usually, late treatment initiations are related to a delayed referral to the specialist, especially for superficial IH. 29 The safety analysis found AEs in 26.6% patients, which is consistent with previous studies on oral propranolol, which reported AEs rates from 19.6% 30 to 38.2%. 31 Sleep disturbances, wheezing and digestive side effects were the most frequently reported AEs in our cohort, as described in the previous studies, however peripheral coldness was not reported in our cohort.…”
Section: Adverse Eventssupporting
confidence: 90%
“…Late Hemangiol initiations >5 months of age concerned 29 subjects in our study. Usually, late treatment initiations are related to a delayed referral to the specialist, especially for superficial IH 29 …”
Section: Discussionmentioning
confidence: 99%
“…2,6 Indeed, the timing of therapy is critical in severe IH because early treatment during the proliferative phase will result in higher response rates, and therefore improve outcomes. 7,8 Many authors have already emphasized the importance of early referral of high-risk IH to multidisciplinary vascular anomaly centers with experienced subspecialists, especially because the discovery of the effectiveness of propranolol for IHs has led to changing treatment decisions in IHs, with more frequent and earlier treatment. 1,9 Unfortunately, clinical studies have revealed that despite the fact that most IH growth is completed at ∼5 months of age, infants are often referred at a later age.…”
mentioning
confidence: 99%